A 2D/2D/2D Ti3C2Tx@TiO2@MoS2 heterostructure as an ultrafast and high-sensitivity NO2 gas sensor at room-temperature. Issue 22 (11th January 2022) - Liu, Zhuo; Lv, He; Xie, Ying; Wang, Jue; Fan, Jiahui; Sun, Baihe; Jiang, Lin; Zhang, Yang; Wang, Ruihong; Shi, Keying
Abstract : A 2D/2D/2D Ti3 C2 T x @TiO2 @MoS2 heterostructure was achieved via a facile one-step hydrothermal strategy; it showed an excellent gas sensing performance to NO2, which is mainly attributed to numerous active sites and unique three-phase heterointerfaces. Abstract : Very diverse two-dimensional (2D) materials have bloomed in NO2 gas sensing applications, which provides new opportunities and challenges in function oriented gas sensors. In this work, a 2D/2D/2D structure of the Ti3 C2 T x @TiO2 @MoS2 composite was well designed via a facile one-step hydrothermal route, in which TiO2 nanosheets are in situ grown on ultrathin and highly conductive Ti3 C2 T x MXene. Simultaneously, the few-layer and vertically oriented MoS2 nanoflakes rich in active edge-sites were uniformly distributed in the composite. Ti3 C2 T x MXene and MoS2 act respectively as the electron reservoir and main sensitive material. The strong interfacial contact in different components facilitated the transfer of charge carriers and their spatial separation. Integrating the unique structural and electronic properties, the as-prepared Ti3 C2 T x @TiO2 @MoS2 sensor exhibited a remarkable gas sensing performance at room temperature ( R a / R g = 55.16, 50 ppm NO2 ), which is 7.3, 3.8 and 2.1 times higher than that of pristine MoS2, TiO2 @MoS2 and Ti3 C2 T x @MoS2 composites, respectively. It also achieved ultrafast response time (1.8 s), more than 90% recoverability, low detection limit (23 ppb), dedicated selectivity and as long as eight-week stability.